2022
DOI: 10.3389/fpubh.2022.844669
|View full text |Cite
|
Sign up to set email alerts
|

Patient's Perception of Digital Symptom Assessment Technologies in Rheumatology: Results From a Multicentre Study

Abstract: IntroductionAn increasing number of digital tools, including dedicated diagnostic decision support systems (DDSS) exist to better assess new symptoms and understand when and where to seek medical care. The aim of this study was to evaluate patient's previous online assessment experiences and to compare the acceptability, usability, usefulness and potential impact of artificial intelligence (AI)-based symptom checker (Ada) and an online questionnaire-based self-referral tool (Rheport).Materials and MethodsPatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…Real-world evidence studies involving real patients have been recommended to examine the performance of symptom checkers against clinicians 27 . The importance of using real-world data within digital health technology development is also strongly supported by regulatory authorities, as evidenced by the introduction of the ‘Real World Evidence’ program by the FDA, which have also approved databases with real-world patient data to support this initiative 31 – 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Real-world evidence studies involving real patients have been recommended to examine the performance of symptom checkers against clinicians 27 . The importance of using real-world data within digital health technology development is also strongly supported by regulatory authorities, as evidenced by the introduction of the ‘Real World Evidence’ program by the FDA, which have also approved databases with real-world patient data to support this initiative 31 – 33 .…”
Section: Discussionmentioning
confidence: 99%
“…A study in California [ 18 ] also examined the mix of patients using Ada in a health system and found that the patient characteristics of users were similar to those of their general patient population but with a younger mean age. A study by Knitza et al [ 38 ] on the use of Ada, a custom diagnostic app (Rheport), and web-based searching for symptoms, showed a high System Usability Scale score of 77.1 for Rheport and a somewhat lower score for Ada of 74.4 ( P <.001). Ratings for “very helpful” or “helpful” were higher for Rheport (65.8% vs 44.3%), although similar numbers would recommend each system to others (79.2% vs 73.3%).…”
Section: Discussionmentioning
confidence: 99%
“…44 Nearly half of all patients used an online search engine prior to their first rheumatology appointment. 12 As current symptom checkers are not very reliable, 14 self-sampling kits could be sent to patients to improve diagnostic accuracy in a second step. These results and any additional diagnostic procedures could be discussed virtually via RMD Open RMD Open RMD Open video consultations.…”
Section: Discussionmentioning
confidence: 99%